Pemberdayaan Masyarakat Desa Masbangun melalui Pendidikan, Kesehatan, Digitalisasi, dan Inovasi - Afani, Afani; Fitriana, Ana; Akhasha, Nadia; Maharani, Rista (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This community service focuses on empowering the community of Masbangun Village, Teluk Batang District, North Kayong Regency, through education, health, digitalization, and innovation. The main problems faced by this village include the lack of English education for elementary school children, the tendency of minors to use gadgets excessively to play games, the lack of an inventory system in the village office, and inadequate health access. To overcome the problem, several programs have been implemented, including English language guidance for elementary school children, socialization of Clean and Healthy Living Behaviors (PHBS), socialization of the negative impact of the use of gadgets as well as training in parental control features, joint healthy gymnastics, creation of an inventory system for goods with village equipment, and training on innovation in making dishwashing soap from concentrates. The results of the program show an improvement in English understanding, although further guidance is still needed for the implementation of PHBS. The healthy gymnastics program and dishwashing soap innovation received a positive response from the public. It is hoped that this program can provide a sustainable impact on the welfare and independence of the Masbangun Village community.